Ceramic Industry of Bangladesh: A Perspective from Porter’s Five Forces Model - Jahan, Nusrat (Journal of Business and Technology (Dhaka), 2012)
Michael Porter’s Five Forces Model is one of the famous tools for analyzing an industry’s environment. According to this model, a company can achieve its existence and success in an industry only if it can overcome and sustain the competitive forces of the market within which it operates. Ceramic industry of Bangladesh is a booming sector and the growth potential of both domestic and local market indicates it may become one of the big foreign exchange earners for the country. Therefore, analyzing the industry environment of ceramic sector is of great concern to strategist since defending against the competitive forces of the marketplace and shaping them in a company’s favor are crucial to strategy formation. To address this issue, this paper analyzes the industry environment (competitive environment) of ceramic sector of Bangladesh by using Porter’s Five forces model. The analysis of five forces indicates that the collective impact of the competitive forces is moderate to weak; hence, the ceramic industry of Bangladesh is considered to be competitively attractive in the sense that industry members can reasonably expect to earn decent profits and a nice return on investment. Keywords: Ceramic Industry; Five forces model; Competitiveness; Attractiveness. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9983 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 104-121